Attachment and wellbeing in women undergoing breast cancer treatment - Alonso, Yolanda; Ezama, Esteban; Fontanil, Yolanda (Anales de Psicología / Annals of Psychology, 2015)
This study investigates the contribution of the attachment to the wellbeing of patients during breast cancer treatment with the aim to provide evidence on how to enhance coping with cancer and its related difficulties. The sample consisted of 58 women who were about to begin radiotherapy for breast cancer. They completed questionnaires about: symptoms and dysfunctions related to disease and treatment, positive and negative affect, emotional wellbeing, daily hassles, and adult attachment. A regression analysis revealed that the component Fear of rejection and abandonment of attachment, the presence of daily hassles ―mainly economic―, and physical symptoms predict the degree of wellbeing. The other two components of attachment (Desire for closeness and Preference for independence) show no significant relationships, and contrary to expectations, the loss of functional capacity does not predict a decrease in wellbeing. We discuss the differential weight of medical and psychosocial variables on health-related quality of life. Results emphasize the importance of interventions aimed at improving emotional state through improved relationships during cancer treatments.